2021
DOI: 10.3390/ijms23010467
|View full text |Cite
|
Sign up to set email alerts
|

Novel Risk Associations between microRNA Polymorphisms and Gastric Cancer in a Chilean Population

Abstract: Gastric cancer (GC) is the fifth leading cause of cancer deaths in the world, with variations across geographical regions and ethnicities. Emerging evidence indicates that miRNA expression is dysregulated in GC and its polymorphisms may contribute to these variations, which has yet to be explored in Latin American populations. In a case-control study of 310 GC patients and 311 healthy donors from Chile, we assessed the association of 279 polymorphisms in 242 miRNA genes. Two novel polymorphisms were found to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Understanding the impact of oncogenic variants across different ethnic groups is crucial as these variants can significantly influence the susceptibility to gastric cancer ( Cordova-Delgado et al, 2021 ; Gonzalez-Hormazabal et al, 2021 ; Landeros et al, 2021 ). This knowledge is essential for prioritizing therapeutic strategies and making informed decisions concerning healthcare economics, public health policies, and global preventive measures.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the impact of oncogenic variants across different ethnic groups is crucial as these variants can significantly influence the susceptibility to gastric cancer ( Cordova-Delgado et al, 2021 ; Gonzalez-Hormazabal et al, 2021 ; Landeros et al, 2021 ). This knowledge is essential for prioritizing therapeutic strategies and making informed decisions concerning healthcare economics, public health policies, and global preventive measures.…”
Section: Discussionmentioning
confidence: 99%
“…The authors demonstrated that the C allele of the mRNA-499 rs3746444 T>C SNP increased susceptibility to GC. Several other SNPs-miR-196a2 rs11614913, miR-27a rs895819, miR-499 rs3746444, miR-27a rs895819, miR-4427 rs701213, miR-548j rs4822739, miR-938 rs12416605, miR-4274 rs1553867776, miR-3175 rs1439619, miR-6891 rs6149511, miR-8084 rs404337, miR-4719 rs7500280 and miR-34b/c rs4938723-have been associated with an increased or decreased susceptibility to GC [58][59][60][61][62]. Interestingly, SNPs have been combined with other parameters to evaluate the correlation with gastric malignancy.…”
Section: Non-coding Rna In Gastric Cancer-their Role As Biomarkers An...mentioning
confidence: 99%
“…As mentioned above, miRNA SNPs could alter the RNA molecular structure. Landeros et al [61] showed that several polymorphisms alter miRNA structure. For example, the miR-6891 rs6149511:T>TGAAGGGCTCCA SNP significantly changes the loop terminal region.…”
Section: Non-coding Rna In Gastric Cancer-their Role As Biomarkers An...mentioning
confidence: 99%